2012
DOI: 10.1177/1066896912437412
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Preoperative Biopsies Compared With Surgical Specimens in the Diagnosis of Colorectal Adenocarcinoma

Abstract: The preoperative biopsy of colorectal adenocarcinoma presented good accuracy compared with histopathological examination of the surgical specimen, but with weak to moderate effective degree of agreement between the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Although TP53 was reviewed in both gastric and colorectal carcinoma, and the agreement between EBs and resection specimen was much higher in gastric carcinoma (κ = 0.94 versus κ = 0.22), however, the reported kappa values are not directly comparable as the threshold for scoring TP53 ‘positive’ differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although TP53 was reviewed in both gastric and colorectal carcinoma, and the agreement between EBs and resection specimen was much higher in gastric carcinoma (κ = 0.94 versus κ = 0.22), however, the reported kappa values are not directly comparable as the threshold for scoring TP53 ‘positive’ differed between the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen (24%) studies reported the number of EBs used for molecular testing; the median (range) mean number of EBs per patient was 2.1 (1 to 6.6 biopsies) . Only one study reported the location within the tumour from which the biopsy was obtained …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations